2020
DOI: 10.1080/00016489.2020.1811999
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory dysfunction in patients after recovering from COVID-19

Abstract: Background: Smell and taste disorders occur in COVID-19 with a high prevalence, but little is known about the duration of the symptoms. In particular, studies using validated olfactory tests are very rare to date. Aims/Objectives: The aim of this study was to determine the olfactory function of COVID-19 recoveries by a detailed olfactory test. Methods: 91 patients with PCR-confirmed, past COVID-19 disease were included. Olfactory history was taken using a questionnaire. Olfactory function was evaluated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
67
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 18 publications
8
67
0
3
Order By: Relevance
“…Our results still showed a portion of participants that remained hyposmic (27%) and similar to the 29% found by Le Bon et al (2020) . A higher percentage of hyposmic was found by Otte et al (2020) after 7 weeks after COVID-19 onset. Discrepancies could be due to several factors such as different study populations, sample size, duration of initial anosmia ( Le Bon et al 2020 ), and days since the onset.…”
Section: Discussionmentioning
confidence: 87%
“…Our results still showed a portion of participants that remained hyposmic (27%) and similar to the 29% found by Le Bon et al (2020) . A higher percentage of hyposmic was found by Otte et al (2020) after 7 weeks after COVID-19 onset. Discrepancies could be due to several factors such as different study populations, sample size, duration of initial anosmia ( Le Bon et al 2020 ), and days since the onset.…”
Section: Discussionmentioning
confidence: 87%
“…The follow-up period, however, was very short and does not allow us to understand the longterm trend of the symptoms. The need for long-term observational results is supported by Otte et al, 8 who acknowledge that there is currently no literary work evaluating the trend of post-infectious olfactory disorder from SARS-CoV-2 several months after onset. In fact, the same authors followed a series of 80 patients for only two months.…”
Section: Discussionmentioning
confidence: 99%
“…4 Several studies have since demonstrated the association between anosmia and SARS-CoV-2 infection. [6][7][8][9] We observed an exponential increase of patients with olfactory deficit in the territory of southern Lombardy (the site of the first European Covid-19 outbreak) between the end of February and the beginning of March, and we consequently described the first series in Europe of patients affected by anosmia during SARS-CoV-2 infection. 3 Klapfenstein et al 6 conducted a study on 114 patients affected by Covid-19, in which 54 (47 per cent) were affected by anosmia.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations